STRATEGI PENDISTRIBUSIAN ZAKAT PASCA PANDEMI COVID-19 di BASNAZ KAB. POLMAN - Norham Hidayat; Rukiah; Nurfitriani (Department of Management Zakat and Waqf, 2023)
The pandemic caused a phenomenon where the economy declined in total which caused the community to be able to survive, with the existence of BAZNAS with the zakat distribution program which is carried out every year it is hoped that it can restore the national economy. This study aims to find out what the zakat distribution strategy is in BAZNAS Kab. Polman after the Covid-19 pandemic and to find out the implementation of the zakat distribution strategy at Baznas Kab. Polman after the Covid-19 pandemic. The type of research used in this research is descriptive qualitative research. The approach used is a phenomenological approach. The results of the study show that the strategy used by Baznas Kab. Polman Dalam is conducting community empowerment, distributing the zakat program, distributing infaq and alms for Covid-19 victims, distributing zakat funds to the medical team, and collaborating with the local government. The implementation of the strategy carried out by Baznas Kab. polman is community empowerment by conducting outreach to the community about zakat, distribution of zakat programs by dividing zakat distribution programs in the form of educational programs, health programs, humanitarian programs, economic programs, and da'wah programs.